E-122 Endovascular embolization of penetrating vessel injury using N-butyl cyanoacrylate. (23rd July 2022) - Morsi, R; Carrión-Penagos, J; Thind, S; Mansour, A; Kramer, C; Lazaridis, C; Goldenberg, F; Prabhakaran, S; Kass-Hout, T
Abstract : Introduction/Purpose: There is limited evidence on the use of N-butyl cyanoacrylate (NBCA) in endovascular embolization of penetrating intracranial and extracranial vessel injuries. We sought to investigate the safety and effectiveness of NBCA in treating these penetrating vessel injuries. Materials and Methods: In a prospectively maintained database, we retrospectively analyzed consecutive patients who presented with a vessel injury caused by a penetrating injury in a large academic Level 1 trauma center between January 1, 2021, and December 31, 2021. We included patients aged ≥ 18 years with any vessel injury in the intracranial or extracranial circulation. The primary endpoint was success of NBCA by absence of vessel perforation and bleeding after embolization via angiogram. The secondary endpoint was recurrence of bleeding via computed tomography (CT) angiogram imaging. Results: A total of 10 patients required endovascular embolization of penetrating vessel injury via NBCA. All patients suffered penetrating vessel injury by a bullet wound. The vessels subject to injury included common carotid artery, internal carotid artery, external carotid artery, vertebral arteries and inferior thyroid arteries. All patients were successfully treated with NBCA with absence of bleeding detected on angiogram. There was no recurrence of bleeding via vessel imaging. Conclusion: To the best of our knowledge, this is the first study demonstrating the safety and effectiveness of NBCA in penetrating vessel injuries. Further research, including observational and randomized trials, is needed to investigate the safety and efficacy in this population. Disclosures: R. Morsi: None. J. Carrión-Penagos: None. S. Thind: None. A. Mansour: None. C. Kramer: None. C. Lazaridis: None. F. Goldenberg: None. S. Prabhakaran: None. T. Kass-Hout: None.